Impact of diabetes duration on heart failure in Korean patients without clinical cardiovascular disease. Issue 9 (March 2019) - Noh, Minsu; Kwon, Hyunwook; Jung, Chang Hee; Lee, Seung-Whan; Lee, Jong-Young; Kim, Min-Ju; Han, Youngjin; Kwon, Tae-Won; Cho, Yong-Pil
Abstract : Abstract: We aimed to investigate the association between diabetes duration and the subsequent occurrence of heart failure (HF) in type 2 diabetes mellitus (T2DM) patients without clinical cardiovascular disease. In this single-center, observational cohort study, a total of 3724 T2DM patients were stratified by diabetes duration into three 5-year interval subgroups. The primary outcomes were the occurrence of new-onset HF and all-cause mortality. HF incidence ( P  < .001) and mortality ( P  = .001) were significantly higher in patients with a longer duration of diabetes (≥10 years) than in those with a shorter duration (<5 years). On multivariate analysis, diabetes duration ≥10 years was not independently associated with all-cause mortality compared with duration < 5 years, but there was a nonsignificant increased risk of HF in patients with a diabetes duration ≥10 years ( P  = .056). Poor glycemic control was associated with an increased risk of HF and mortality; statin use was associated with a significantly decreased risk of mortality. Our study indicated that a longer duration of diabetes is associated with an increased risk of new-onset HF occurrence and all-cause mortality in T2DM patients without clinical cardiovascular disease.